Influence of chain length of long-chain fatty acid surfactant on the thermal conductivity of magnetite nanofluids in a magnetic field - Dadwal, Arun; Dadwal, Arun (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Stable magnetic nanofluids are prepared by dispersing long-chain fatty acid surfactants coated magnetite (Fe3O4) nanoparticles in toluene and investigated the effect of chain length of the surfactant molecules on the thermal conductivity of the magnetite nanofluids in a magnetic field. Superparamagnetic magnetite nanoparticles having a comparable particle size (similar to 10 nm) are coated with three different long-chain fatty acid surfactants; myristic acid (C13H27COOH), palmitic acid (C15H31COOH) and stearic acid (C17H35COOH). The thermal conductivity of the nanofluids, in a magnetic field, is found to decrease with increasing the chain length of the surfactant molecule. Among the three fluids, the shorter chain myristic acid coated nanofluid showed larger enhancement in the thermal conductivity at smaller fields as compared to the other fluids. The results indicated that the chain length of the surfactant molecule present on the surface of the magnetite nanoparticles affect the thermal conductivity of the magnetic nanofluid in an external magnetic field, due to the difference in the extent of interdigitation of the surfactant molecules.

Integrating structurally perfect s=1/2 kagome-lattice with reduced graphene oxide - Gupta, Kriti; Dadwal, Arun; Ninawe, Pranay; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry C, 2020)
S = 1/2 kagome-lattice hydroxychlorides are promising candidates for realizing the elusive quantum spin liquid (QSL) state. Herbertsmithite [Cu3Zn(OH)(6)Cl-2], a naturally occurring hydroxychloride mineral from the class of atacamites {[Cu-4-xMx(OH)(6)X-2] where M = Zn, Cu, Co, Ni and X = Cl, Br, I}, is one of the most appealing systems to study the QSL state because of the presence of a structurally perfect S = 1/2 kagome-lattice. It is an electrical insulator. However, realizing phase-pure herbertsmithite without imposing harsh reaction conditions remained synthetically challenging. In this work, for the first time, we have synthesized phase-pure herbertsmithite as well as its structural analogue paratacamite, [ZnxCu4-x(OH)(6)Cl-2; 0.33 = x < 1], at ambient reaction conditions. Furthermore, taking graphene oxide (GO) as an additional precursor in the reaction mixture, we have successfully integrated phase-pure crystallites of herbertsmithite (H) and paratacamite (P) with nanosheets of semiconducting and diamagnetic reduced graphene oxide (rGO) by in situ oxidation-reduction reaction. The isolated H-rGO and P-rGO systems were found to be magnetic semiconductors inheriting strong spin frustration from H and P, and semiconductivity from rGO. The H-rGO system in particular exhibited negative Seebeck coefficient (n-type semiconductor) with a thermoelectric power factor of 0.1 mu W center dot m(-1)center dot K-2 at 400 K. We anticipate the simple chemical principles outlined in this work to be useful for studying a variety of complex QSLs including electron doping. Also, semiconducting and rather unconventional materials of such metal oxochlorides with rGO isolated here need further exploration in view of thermoelectric applications.